EVALUASI PENGGUNAAN OBAT ANTITUBERKULOSIS PARU DIPUSKESMAS: NARRATIVE LITERATURE REVIEW - Rohendiputri, Isyaura Bellafasya; Wahyuningsih, Sri (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. While it primarily affects the lungs, it can also impact other organs. In Indonesia, pulmonary TB remains a significant health issue. This study aims to evaluate the use of anti-tuberculosis medications at various community health centers (puskesmas) in Indonesia through a literature review. The research method employed involves a literature review with searches conducted on Google Scholar and PubMed databases. Out of 360 articles found on Google Scholar and 13,026 articles on PubMed, 8 relevant articles were identified for this study. The results indicate that the most commonly used treatment regimen is Category 1, which includes a 2-month intensive phase with a combination of Isoniazid 75 mg, Rifampicin 150 mg, Pyrazinamide 400 mg, and Ethambutol 275 mg, followed by a 4-month continuation phase with Rifampicin 150 mg and Isoniazid 150 mg. This medication regimen aligns with the Tuberculosis Control Guidelines issued by the Indonesian Ministry of Health in 2016. The evaluation shows that Indonesian puskesmas generally adhere to the established treatment guidelines but still require further monitoring to ensure adherence and effectiveness of the treatment.